Students’ online interaction, self-regulation, and learning engagement in higher education: The importance of social presence to online learning - Jia Miao; Li Ma (Frontiers in Psychology, 2022)
Online learning have played a very significant role for achieving professional and academic qualifications in higher education. There have been more and more researches that explore the issues of learning activities, satisfaction, engagement, and interactions between instructors and students. To promote learning engagement in online learning environments in higher education, this study collected data from 334 full-time undergraduate students in a large public Chinese university and explored the correlation of online interaction, self-regulation learning and social presence on learning engagement in online environments. The research findings indicated that online interaction affected social presence and indirectly affected learning engagement through social presence. In addition, social presence affected learning engagement, self-regulation affected social presence, and social presence also mediated the relationship between self-regulation and learning engagement. This study reported that self-regulation learning and social presence had positive correlation with on students’ learning engagement in online environments. The findings of this study have significant practical implications for teaching practices.